Unlawfulness Within the Bugo Tradition in Morotai: A Comparative Perspective of Positive Criminal Law & Islamic Criminal Law - Rahmat Abdullah; Abdul Mutalib; Andri Sutrisno; Agnes Fitryantica; Arikha Saputra (AHKAM : Jurnal Ilmu Syariah, 2026)
The Bugo tradition in Sangowo Village, Morotai Island Regency, is the practice of taking fruit or goods from someone's garden by leaving a sign as notification to the owner. This practice raises legal issues when confronted with theft under the Criminal Code and sariqah in fiqh al-jināyāt. This study employs a legal-empirical or socio-legal method with conceptual and comparative approaches to analyse Bugo's legal status from the perspectives of positive and Islamic criminal law. The results show that although Bugo formally fulfills the elements of Article 476 of the Criminal Code, its material unlawfulness is nullified because it is a living law accepted by the community and qualifies as a reason for criminal exemption outside the law. From the fiqh al-jināyāt perspective, Bugo does not fulfill the elements of khufyah and qaṣd al-sariqah, while strong shubhah from ʿurf nullifies the ḥadd based on the rule of "idrāʾ al-ḥudūd bi al-shubuhāt" (ḥudūd are averted by doubt). Both legal systems have flexible safety valves and consider social context, yet differ in focus: positive criminal law nullifies the act's unlawful nature, whereas Islamic criminal law nullifies the ḥadd penalty even when the act remains shubhah.   Abstrak Tradisi Bugo di Desa Sangowo, Kabupaten Pulau Morotai, adalah praktik mengambil buah atau barang dari kebun milik orang lain dengan meninggalkan tanda sebagai pemberitahuan kepada pemiliknya. Praktik ini menimbulkan problematika yuridis ketika dihadapkan pada delik pencurian dalam KUHP dan delik sariqah dalam fikih jinayat. Penelitian ini menggunakan metode yuridis-empiris atau socio-legal research dengan pendekatan konseptual serta pendekatan komparatif untuk menganalisis status hukum tradisi Bugo dalam perspektif hukum pidana positif dan hukum pidana Islam. Hasil analisis menunjukkan bahwa meskipun tradisi bugo secara formil memenuhi unsur delik Pasal 476 KUHP, sifat melawan hukum materiilnya gugur karena merupakan living law yang diterima masyarakat dan dapat dikualifikasikan sebagai alasan penghapus pidana di luar undang-undang. Dalam perspektif fikih jinayat, tradisi Bugo tidak memenuhi unsur khufyah dan qaṣd al-sariqah, serta menimbulkan shubhah yang kuat dari ʿurf yang menggugurkan ḥadd berdasarkan kaidah “idrāʾ al-ḥudūd bi al-shubuhāt”. Kedua sistem hukum memiliki katup pengaman yang fleksibel dan mempertimbangkan konteks sosial, namun berbeda dalam fokus: hukum pidana positif menggugurkan sifat melawan hukum perbuatan, sementara hukum pidana Islam menggugurkan sanksi ḥadd meskipun perbuatan masih bersifat shubhah.